Кримська проблема в українсько-російських міждержавних відносинах 1990-х рр. - Рибак, Н. Б. (Видавництво Львівської політехніки, 2014)
Розкрито суть кримської проблеми в українсько-російських міждержавних відно- синах 1990-х років. Її специфіка була визначена глобальними процесами: ліквідацією системи східноєвропейського соціалізму і двополюсного поділу світу, розпадом СРСР, історичною нетрадиційністю економічного і політико-правового оформлення України і Росії як незалежних держав, а також вибору ними геополітичних стратегій. The occupation of the Crimea in March, 2014 by the Russian Federation updates versatile understanding of the Crimean issue in the context of territorial, military, political, economic, and geopolitical tensions in Ukrainian-Russian intergovernmental relations. The article reveals the essence of Ukrainian-Russian interstate misunderstandings of the 1990s concerning the Crimea and their legal framework. It is noted that the complexity of the problem, and hence its ambiguity and in many cases a complete alternative treatment options or concrete steps to address the authorities of Ukraine and Russia (in fact based on a single political and legal documentary framework of the late 1940s – early 1990s) were caused by changes in socio-economic and political conditions under which the problem originated, was realized, became topical and practically solved. Representatives of the legislative power of Russia stressed the legal illegitimacy of the transfer of the Crimean region to Ukraine in 1954 and, thus, the absolute right of Russia to the Crimea and Sevastopol as a base of the Russian Black Sea Fleet. For its part, Ukraine, refuting these claims put forward counterarguments that the Crimea together with Sevastopol belonged to Ukraine. Specificity of the “Crimean problem” at the international level in the 1990s was determined by global processes: elimination of systems of Eastern European socialism and bipolar division of the world, the collapse of the USSR, historically non-traditional approach to economic, political and legal formation of Ukraine and Russia as independent states, as well as their choice of geopolitical strategies. The peculiarity of this problem was the importance of distant economic interests or political aim of the participants of the official Ukrainian-Russian relations of the 1990s engaged in finding solutions to it. Transition situation of the political system, the uncertainty of its social and legal foundations resulted in temporary tactical alliances, extremely ideological approaches, multiplicity of standards in dealing with territorial and military issues, which after receiving legal registration (bilateral and multilateral agreements, contracts etc.) created political and legal framework for further contradictions and conflicts. The large-scale Ukrainian-Russian Treaty on Friendship, Cooperation and Partnership, signed in March, 1997 became a peculiar finale of the Ukrainian-Russian relations of the 1990s. The signed treaty, in fact, secured sovereignty and territorial integrity of Ukraine on the part of Russia, but on the other hand legalization of the long-term stay of the Russian Fleet in the Crimea enabled the RF to gain control of the part of the Ukrainian territory, maritime communication, airspace, and hence to have a considerable impact on Ukraine’s foreign policy. Especially negative effects for Ukraine were saving the Russian military presence in the Crimea and exercising military control over the peninsula. The latter, in fact, greatly facilitated the implementation of Russian military aggression and annexation of the Crimea in February-March, 2014, which was a major violation of basic norms of international law, in particular the UN Charter, the provisions of the Helsinki Final Act, Budapest Memorandum of 1994, and bilateral Ukrainian-Russian international treaties.
Keywords: Крим; Севастополь; Чорноморський флот; Україна; Росія; кримська проблема; міждержавні відносини; the Crimea; Sevastopol; Ukraine; Russia; the Black Sea Fleet; the Crimean problem; inter-state relations